(untitled) (Annals of Medical Research, 2021)
Aim: The study aimed to evaluate the relationship between the caries frequency, which was determined using different caries indexes Objective: The aim of this study was to investigate the effect of in-office bleaching agents on the color and translucency of different resin composites. Materials and Methods: Twenty-four disk-shaped specimens with 1 mm thickness and 8 mm diameter were fabricated from five different resin composites. The specimens were then divided into three subgroups, two office bleaching groups (40% Opalescence Boost, 38% Whitesmile Power Whitening) and one control group (n=8). All specimens were polymerized for 40 s with a LED light-curing unit. Color measurement was performed using a spectrophotometer. Bleaching agents were applied to the experimental groups in accordance with the manufacturer’s instructions for 14 days, while the specimens in the control group were kept in distilled water only. Translucency parameters of the specimens before and after bleaching and the color changes after bleaching were calculated using CIE L*a*b* color coordinates. Data were analyzed using the paired sample t-test and ANOVA (α=0.05).Results: Statistically significant differences were found between the control group and the bleached groups according to color change values (p0.05). The highest mean color change value was observed in the Ceram-X / Opalescence Boost group. The Ceram-X / Opalescence Boost, Majesty Esthetic / Opalescence Boost, and Ceram-X / Whitesmile Power specimens showed clinically non-acceptable color changes. Translucency parameter values in each group between baseline and the end of the 14th day revealed no statistically significant difference (p>0.05).Conclusions: The office bleaching agents may affect the color and translucency parameters of composite resins depending on the structural properties.